THE STUDENTS’ PERCEPTION OF REWARDS AND PUNISHMENT TOWARD THEIR MOTIVATION IN ENGLISH LEARNING - Ulfaminingsih; St. Asriati AM; Muhammad Asrianto Setiadi (FKIP Unismuh Makassar, 2021)
This research was conducted to determine students' perceptions and effect of reward and punishment for their motivation in learning English. This study reveals that students' perceptions of reward and punishment in learning English are something that is very fun and enjoyable when applied in the learning process because it can increase enthusiasm for learning. The effect of rewards and punishment on student motivation in learning English are: first, reward increases student motivation to be more active in learning, second, the reward increases students' interest in English subjects; and third, rewards motivate students to repeat their good achievements. Regarding the effect of punishment on student motivation, this study found that punishment has various effects on student motivation. First, punishment also increases student motivation to be more diligent in study. When the teacher punishes students, they are triggered to do or do better to prove to other students that they are able to improve their achievement in English learning. Second, punishment prevents students from repeating the same action or behavior again. Students try to arrive on time after they are deemed late for class, and they will pay more attention to teacher warnings after being punished. Third, punishment turned out to make students feel embarrassed, lose self-confidence, and feel nervous about being in a school environment.